Psoas abscess presenting as a bowel obstruction in a child: A case report - Thuy-Ngan; Khoa Nguyen-Dang; Ngoc Duong-Minh; Hanh-Duy; Minh-Hon (Elsevier, 2024)
Introduction: Psoas abscess (PA) is an uncommon condition in children where pus accumulates in the psoas muscle. The disease symptoms are subtle and nonspecific, often causing delayed diagnosis. Case presentation: Our case describes an unusual manifestation of PA caused by methicillin-resistant Staphylococcus aureus (MRSA) when an 11-year-old male patient was admitted with suspected bloodstream infection from the gastrointestinal tract and bowel obstruction following closed trauma from a bicycle fall. An emergency laparotomy revealed turbid abdominal fluid with pseudomembranes and no apparent cause of peritonitis was found upon observing the entire abdominal cavity. On the fourth day after admission, blood, sputum, and peritoneal fluid cultures were all positive for MRSA. Despite broad-spectrum antibiotic treatment targeting MRSA, the patient's clinical condition did not improve. PA was confirmed via abdominal computed tomography on the ninth-day post-hospitalization with a persistent MRSA bloodstream infection. Successful treatment of PA was achieved through open surgery. The patient's condition improved and was discharged on the 40th day after admission. Conclusion: PA can present as bowel obstruction. Therefore, PA should be ruled out in patients with bowel obstruction of unknown etiology, especially if the patient has a history of trauma to the hip region.